Physical Activity, Sedentary Leisure Time, Circulating Metabolic Markers, and Risk of Major Vascular Diseases. (September 2019) - Pang, Yuanjie; Kartsonaki, Christiana; Du, Huaidong; Millwood, Iona Y.; Guo, Yu; Chen, Yiping; Bian, Zheng; Yang, Ling; Walters, Robin; Bragg, Fiona; Lv, Jun; Yu, Canqing; et al.
Abstract : Background: Physical inactivity and sedentary behavior are associated with higher risk of cardiovascular disease (CVD). Little is known about the relevance of circulating metabolites for these associations. Methods: A nested case-control study within the prospective China Kadoorie Biobank included 3195 incident CVD cases (2057 occlusive CVD and 1138 intracerebral hemorrhage) and 1465 controls aged 30 to 79 years without prior CVD or statin use at baseline. Nuclear magnetic resonance spectroscopy was used to measure 225 metabolic markers and derived traits in baseline plasma samples. Linear regression was used to relate self-reported physical activity and sedentary leisure time to biomarkers, adjusting for potential confounders. These were contrasted with associations of biomarkers with occlusive CVD risk. Results: Physical activity and sedentary leisure time were associated with >100 metabolic markers, with patterns of associations generally mirroring each other. Physical activity was inversely associated with very low and low-density and positively with large and very large HDL (high-density lipoprotein) particle concentrations. Physical activity was also inversely associated with alanine, glucose, lactate, acetoacetate, and the inflammatory marker glycoprotein acetyls. In general, associations of physical activity and sedentary leisure time with specific metabolic markers were directionally consistent with the associations of these metabolic markers with occlusive CVD risk. Overall, metabolic markers potentially explained ≈70% of the protective associations of physical activity and ≈50% of the positive associations of sedentary leisure time with occlusive CVD. Conclusions: Among Chinese adults, physical activity and sedentary behavior have opposing associations with a diverse range of circulating metabolites, which may partially explain their associations with CVD risk. Abstract : Supplemental Digital Content is available in the text.